Variance in Factors Influencing Buyer Behaviour Across Various Product Categories in FMCGs - Siji, Smitha (Indian Journal of Marketing, 2015)
FMCGs are not a single product. It is an umbrella term that holds together a number of different products. It includes cosmetics and toiletries, personal care products, household fabric care products, household cleaners, food products, and so forth. They are considered to be a low involvement product category, and all theories and models in consumer behavior are applied to this sector considering it to be as one product category. But is it really like that? Does the customer show the same kind of behavior while buying a perfume and while buying a toilet cleaner? This study attempts to find answers to these questions. A sample size of 537 households was selected for the survey. Hypotheses were derived from the literature reviewed for the study and were tested. The factors identified are price perception, loyalty to local retailers, and purchase decision involvement. Reliability and validity of the instrument were also tested. ANOVA was used to find out the differences among these factors across the various sub-categories in FMCGs. This study is all the more significant in the wake of current developments in the field of retailing. The findings will help in devising appropriate strategies to sell FMCG products to customers.